A wall filling material using barium sulfate waste residue and preparation method thereof

Through acidification treatment and polypropylene fiber fixation technology, the barium slag is treated harmlessly and formed into reinforced polypropylene fiber materials, which solves the problems of high barium slag processing costs and safety risks, and improves the performance of wall filling materials.

CN118495883BActive Publication Date: 2025-01-24CHONGQING LUYU MINING DEV CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410638355.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-01-24
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

In the prior art, the harmless treatment cost of barium slag is relatively high, and there are safety risks in resource utilization.

Method used

The mineral waste residue is treated harmlessly through acidification treatment to generate free barium ion solution and insoluble waste residue, and the free barium ion is fixed through modified polypropylene fiber to form a reinforced polypropylene fiber material, which is mixed with barium sulfate waste residue and other materials. Form wall filling material.

Benefits of technology

It improves the comprehensive performance of filling materials, significantly enhances the crack resistance and pressure resistance of wall filling materials, reduces the cost of harmless treatment, and reduces safety risks in resource utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118495883B_ABST
    Figure CN118495883B_ABST
Patent Text Reader

Abstract

The invention discloses a wall filling material using barium sulfate waste residue in the field of barium sulfate recovery and a preparation method thereof, comprising the following components in parts by weight: 550-650 parts of coarse aggregate, 200-300 parts of barium sulfate waste residue, 250-300 parts of cement, 1.5-2 parts of polycarboxylate water reducer, 1.5-2 parts of reinforced polypropylene fiber, and 80-120 parts of water. The invention performs harmless treatment on the ore source waste residue by acidification treatment, recycles the ore source waste residue to generate free barium ion solution and insoluble waste residue, fixes the free barium solution by modified polypropylene fiber, generates reinforced polypropylene fiber material, mixes the material with barium sulfate waste residue and other materials to form wall filling material, and can improve the comprehensive performance of the filling material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of barium sulfate recovery, and specifically refers to a wall filling material utilizing barium sulfate waste residue and a preparation method thereof. Background Art

[0002] In the chemical industry, the production method of barium carbonate is mainly based on the carbonization reduction method. Its principle is to reduce the barium sulfate in the barite and the carbon in the coal powder to generate barium sulfide, hydrolyze the barium sulfide to generate hydrogen sulfide and barium hydroxide, and then react with carbon dioxide to generate barium carbonate. The production process mainly includes: mixing and crushing the barite with the coal powder grade, placing it in a rotary kiln for high-temperature sintering to form barium sulfide, circulating the dilute brine into the crude barium pool, soaking the dilute brine for a certain period of time to obtain concentrated brine, and the remaining waste is barium slag. The concentrated brine is driven into a carbonization tower, and carbon dioxide is introduced to obtain barium carbonate slurry. The barium slurry is washed, filtered, and supported by barium cakes, which are then packaged after drying to obtain industrial barium carbonate. According to statistics from existing technologies, each production of 1 Tons of barium carbonate accumulate 0.87 tons of barium slag each year. The elements in the barium slag, as long as they are barium, exist in the form of barium sulfate and barium carbonate, and are acid-soluble and water-soluble. The pH value of the barium slag sample is relatively high, close to 12-13. Since barium slag is corrosive and strongly alkaline, it has certain toxicity in the ecological environment and is a hazardous waste. It needs to be converted into ordinary industrial solid waste for reuse. The barium slag can be used for wastewater treatment after harmless treatment. After mixing the barium slag with other compounds such as limestone, it can purify phosphorus-containing and chromium-containing wastewater, and can also be used to make building materials. The barium slag contains many cement clinker minerals and is alkaline. It can be mixed with lime footings, slag, etc. to make composite silicate cement.

[0003] The existing technologies currently have the following main problems: 1) The cost of harmless treatment of barium slag is relatively high; 2) There are safety risks in the resource utilization of barium slag. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a wall filling material using barium sulfate waste slag and a preparation method thereof. The present invention performs harmless treatment on the mineral waste slag through acidification treatment, recycles the mineral waste slag to generate free barium ion solution and insoluble waste slag, fixes the free barium solution through modified polypropylene fiber to generate enhanced polypropylene fiber material, and mixes the enhanced polypropylene fiber material with barium sulfate waste slag and other materials to form a wall filling material, which can improve the comprehensive performance of the filling material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention proposes a wall filling material using barium sulfate waste residue, and the wall filling material comprises the following components in parts by weight:

[0006] 550-650 parts of coarse aggregate, 200-300 parts of barium sulfate waste residue, 250-300 parts of cement, 1.5-2 parts of polycarboxylate water reducer, 1.5-2 parts of reinforced polypropylene fiber, 80-120 parts of water;

[0007] Preferably, the barium sulfate waste residue is obtained by harmless treatment of mineral waste residue, and the specific method comprises the following steps:

[0008] S1, crushing the barium slag to obtain pretreated barium slag;

[0009] S2, placing the pretreated barium slag described in step S1 in a beaker, adding hydrochloric acid, adjusting the temperature to 60-70° C., placing on a magnetic stirrer at 450-500 rpm for leaching for 2-3 hours, filtering, washing, and collecting the filtrate to obtain a barium slag leaching solution;

[0010] S3, taking the barium slag leaching solution prepared in step S2, adjusting the pH to 5.8-6.2 with barium carbonate, adjusting the pH to 8.9-9.1 with barium hydroxide solution, filtering, collecting the filtrate as a high-purity barium solution after solid-liquid separation, collecting the filter residue, adding calcium hydroxide, adjusting the pH of the filter residue to 7.5-8, and obtaining barium sulfate waste residue;

[0011] Preferably, in step S1, the grinding fineness of the pretreated barium slag is -0.074, accounting for 70%-80%;

[0012] Preferably, in step S2, the hydrochloric acid concentration is 2-3 mol / L;

[0013] Preferably, in step S2, the solid-liquid ratio between the pretreated barium slag and the hydrochloric acid is 1:5-7;

[0014] Preferably, the method for preparing the reinforced polypropylene fiber specifically comprises the following steps:

[0015] S4, dissolving AMPS and acrylic acid in anhydrous ethanol, adjusting the pH value to 6.5-7.0, adding polypropylene, adding ammonium persulfate, heating to 80-100°C in a sealed nitrogen environment for reaction for 15-20 minutes, then adding oxidized polyethylene wax and vinyl triethoxysilane, mixing evenly, removing the solution, and obtaining a polypropylene fiber precursor;

[0016] S5, mixing the polypropylene fiber precursor prepared in step S4 with the high-purity barium solution prepared in step S3, stirring at a speed of 400-500 rpm, raising the reaction temperature to 60-80° C., reacting for 80-100 min, removing excess solvent, and obtaining a reinforced polypropylene blend;

[0017] S6, placing the enhanced polypropylene blend prepared in step S5 in a dynamic vacuum oven for drying, extruding it with a twin-screw common mixing extruder at a temperature of 220-240° C., spinning it with a pore size of 0.3-0.5 mm, and cutting it to obtain enhanced polypropylene fibers;

[0018] Preferably, in step S4, the components in the raw material include, by weight: 1.5-2 parts of acrylic acid, 0.5-0.8 parts of AMPS, 8-10 parts of polypropylene, 1-3 parts of oxidized polyethylene wax, and 3-5 parts of vinyl triethoxy silane;

[0019] Preferably, in step S4, the mass concentration of acrylic acid in anhydrous ethanol is 25-30 g / L;

[0020] Preferably, in step S4, the amount of ammonium persulfate added is 1.25%-1.5% of acrylic acid;

[0021] Preferably, in step S5, the amount of polypropylene fiber precursor added to the high-purity barium solution is 50-70 g / L;

[0022] Preferably, in step S6, the length of the reinforced polypropylene fiber is 50-80 mm;

[0023] The present invention also provides a method for preparing a wall filling material using barium sulfate waste residue, which specifically comprises the following steps:

[0024] S7, mixing the coarse aggregate, barium sulfate waste residue and cement at a speed of 40 rpm for 1-2 minutes;

[0025] S8, add water reducing agent and water, stir at 60-65rpm, and mix well;

[0026] S9. Add reinforced polypropylene fiber and stir at 80-85 rpm to obtain a wall filling material.

[0027] The beneficial effects achieved by the present invention are as follows:

[0028] The invention provides a wall filling material using barium sulfate waste residue and a preparation method thereof. The invention performs harmless treatment on the mineral waste residue by acidification treatment, recycles the mineral waste residue to generate free barium ion solution and insoluble waste residue, fixes the free barium solution by modified polypropylene fiber, generates enhanced polypropylene fiber material, mixes the enhanced polypropylene fiber material with barium sulfate waste residue and other materials to form a wall filling material, and can improve the comprehensive performance of the filling material; the invention uses AMPS and acrylic acid to entangle with polypropylene in an in-situ polymerization mode, introduces carboxyl groups and sulfonyl groups into polypropylene molecules, and after mixing the polypropylene molecules with high-purity barium ion solution, the carboxyl groups and sulfonyl groups can be combined with barium ions to form solid particles attached to the surface of polypropylene fibers, play a role in reinforcing fibers, avoid a large amount of agglomeration of polypropylene fibers in concrete, and can significantly enhance the crack resistance and compression resistance of the wall filling material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The SEM images of the reinforced polypropylene fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0030] Figure 2 The shrinkage performance results of the wall filling materials prepared in the experimental examples and comparative examples of the present invention are shown in FIG.

[0031] Figure 3 This is a graph showing the splitting tensile performance results of the wall filling materials prepared in the experimental examples and comparative examples of the present invention.

[0032] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0035] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.

[0036] The sources of materials used in the embodiments of the present invention are as follows:

[0037] The coarse aggregate is limestone;

[0038] Mineral barium slag comes from Chongqing Luyu Mining Co., Ltd. It is the barium slag produced after the barite industry extracts barium carbonate. The composition analysis results are shown below:

[0039] Components B S <![CDATA[BaCO 3 ]]> <![CDATA[BaSO 4 ]]> <![CDATA[SiO 2 ]]> CaO <![CDATA[Fe 2 THE 3 ]]> <![CDATA[Al 2 THE 3 ]]> MgO other content% 2.63 25.86 21.33 12.37 7.44 5.53 4.85 2.12 14.87

[0040] Cement uses the same P·O45.2 ordinary Portland cement;

[0041] Example 1

[0042] This embodiment provides a wall filling material using barium sulfate waste residue, and the wall filling material specifically includes the following components in parts by weight:

[0043] 550 parts of coarse aggregate, 200 parts of barium sulfate waste residue, 300 parts of cement, 2 parts of polycarboxylate water reducer, 1.5 parts of reinforced polypropylene fiber, and 120 parts of water;

[0044] The method for harmless treatment of mineral waste residue specifically comprises the following steps:

[0045] S1. The mineral barium slag is passed through a 5-mesh sieve, crushed by a jaw crusher, passed through a 200-mesh sieve, and the grinding fineness of the screened barium slag is -0.074, accounting for 70%, to obtain pre-treated barium slag;

[0046] S2, placing 10 g of the pretreated barium slag described in step S1 in a beaker, adding 2 mol / L hydrochloric acid solution according to a solid-liquid ratio of 1:5, raising the leaching temperature by 60°C, transferring to a magnetic stirrer and leaching at a speed of 480 rpm for 2 hours, filtering, washing the precipitate, checking with a silver nitrate solution for the absence of chloride ions, collecting the filtrate, and obtaining a barium slag leaching solution;

[0047] S3, adding barium carbonate to the barium slag leachate to neutralize excess hydrochloric acid, adjusting the pH of the leachate to 6.0, and then adding 0.5 mol / L barium hydroxide solution dropwise to adjust the pH to 9.0, precipitating other metal ions in the solution, filtering, performing solid-liquid separation, collecting the filtrate as a high-purity barium solution, collecting the filter residue, adding calcium hydroxide and mixing evenly, adjusting the pH of the filter residue to 8.0, and obtaining a barium sulfate filter residue;

[0048] The preparation method of the reinforced polypropylene fiber specifically comprises the following steps:

[0049] S4. Accurately weigh 1.5 g of acrylic acid and 0.5 g of AMPS in a flask, add 50 mL of anhydrous ethanol and stir until dissolved, adjust the pH to 7, add 8 g of polypropylene to the reaction system, add 20 mg of ammonium persulfate, introduce nitrogen to replace the aerobic environment in the reaction system, raise the temperature of the reaction system to 80° C. in a sealed environment, mix the reaction system thoroughly, react for 20 min, immediately add 1 g of oxidized polyethylene wax and 3 g of vinyl triethoxysilane, mix, and after the reaction system cools to room temperature, dry and remove the solution to obtain a polypropylene fiber precursor;

[0050] S5, placing 10 g of the polypropylene fiber precursor prepared in step S4 in a beaker, heating to 50° C., adding 200 mL of the high-purity barium solution prepared in step S3, placing on a stirrer, stirring at a speed of 400 rpm, raising the reaction temperature to 80° C., continuing to stir the reaction for 80 min, and after the reaction system is cooled to room temperature, freeze-drying to remove excess solvent to obtain an enhanced polypropylene blend;

[0051] S6, placing the enhanced polypropylene blend prepared in step S5 in a dynamic vacuum oven for drying, extruding it at a temperature of 230° C. using a twin-screw common mixing extruder, spinning it with a pore size of 0.4 mm, and cutting it into enhanced polypropylene fibers with a length of 50 mm;

[0052] The present invention also provides a preparation method using barium sulfate waste residue and wall filling material, which specifically comprises the following steps:

[0053] S7, mixing the coarse aggregate, barium sulfate waste residue and cement at a speed of 40 rpm for 2 min;

[0054] S8, add water reducing agent and water, stir at 65 rpm, and mix well;

[0055] S9. Add reinforced polypropylene fiber and stir at 80 rpm to obtain a wall filling material.

[0056] Example 2

[0057] This embodiment provides a wall filling material using barium sulfate waste residue, and the wall filling material specifically includes the following components in parts by weight:

[0058] 600 parts of coarse aggregate, 200 parts of barium sulfate waste residue, 250 parts of cement, 1.5 parts of polycarboxylate water reducer, 2 parts of reinforced polypropylene fiber, and 100 parts of water;

[0059] The method for harmless treatment of mineral waste residue specifically comprises the following steps:

[0060] S1. The mineral barium slag is passed through a 5-mesh sieve, crushed by a jaw crusher, passed through a 200-mesh sieve, and the grinding fineness of the screened barium slag is -0.074, accounting for 80%, to obtain pretreated barium slag;

[0061] S2, placing 10 g of the pretreated barium slag described in step S1 in a beaker, adding 2 mol / L hydrochloric acid solution according to a solid-liquid ratio of 1:7, raising the leaching temperature to 70°C, transferring to a magnetic stirrer and leaching at a speed of 450 rpm for 3 hours, filtering, washing the precipitate, checking with a silver nitrate solution for the absence of chloride ions, collecting the filtrate, and obtaining a barium slag leaching solution;

[0062] S3, adding barium carbonate to the barium slag leachate to neutralize excess hydrochloric acid, adjusting the pH of the leachate to 5.8, then adding 0.5 mol / L barium hydroxide solution dropwise, adjusting the pH to 9.1, precipitating other metal ions in the solution, filtering, performing solid-liquid separation, collecting the filtrate as a high-purity barium solution, collecting the filter residue, adding calcium hydroxide and mixing evenly, adjusting the pH of the filter residue to 8.0, and obtaining a barium sulfate filter residue;

[0063] The preparation method of the reinforced polypropylene fiber specifically comprises the following steps:

[0064] S4. Accurately weigh 2 g of acrylic acid and 0.5 g of AMPS in a flask, add 80 mL of anhydrous ethanol and stir until dissolved, adjust the pH to 6.5, add 10 g of polypropylene to the reaction system, add 25 mg of ammonium persulfate, introduce nitrogen to replace the aerobic environment in the reaction system, raise the temperature of the reaction system to 80° C. in a sealed environment, mix the reaction system thoroughly, react for 20 min, immediately add 2 g of oxidized polyethylene wax and 5 g of vinyl triethoxysilane, mix, and after the reaction system cools to room temperature, dry and remove the solution to obtain a polypropylene fiber precursor;

[0065] S5, placing 10 g of the polypropylene fiber precursor prepared in step S4 in a beaker, heating to 50° C., adding 200 mL of the high-purity barium solution prepared in step S3, placing on a stirrer, stirring at a speed of 500 rpm, raising the reaction temperature to 90° C., continuing to stir the reaction for 90 min, and after the reaction system is cooled to room temperature, freeze-drying to remove excess solvent to obtain an enhanced polypropylene blend;

[0066] S6, placing the enhanced polypropylene blend prepared in step S5 in a dynamic vacuum oven for drying, extruding it at a temperature of 220° C. using a twin-screw common mixing extruder, spinning it with a pore size of 0.5 mm, and cutting it into enhanced polypropylene fibers with a length of 70 mm;

[0067] The present invention also provides a preparation method using barium sulfate waste residue and wall filling material, which specifically comprises the following steps:

[0068] S7, mixing the coarse aggregate, barium sulfate waste residue and cement at a speed of 40 rpm for 2 min;

[0069] S8, add water reducing agent and water, stir at 65 rpm, and mix well;

[0070] S9. Add reinforced polypropylene fiber and stir at 85 rpm to obtain a wall filling material.

[0071] Example 3

[0072] This embodiment provides a wall filling material using barium sulfate waste residue, and the wall filling material specifically includes the following components in parts by weight:

[0073] 650 parts of coarse aggregate, 200 parts of barium sulfate waste residue, 300 parts of cement, 1.8 parts of polycarboxylate water reducer, 1.5 parts of reinforced polypropylene fiber, and 120 parts of water;

[0074] The method for harmless treatment of mineral waste residue specifically comprises the following steps:

[0075] S1. The mineral barium slag is passed through a 5-mesh sieve, crushed by a jaw crusher, passed through a 200-mesh sieve, and the grinding fineness of the screened barium slag is -0.074, accounting for 70%, to obtain pre-treated barium slag;

[0076] S2, placing 10 g of the pretreated barium slag described in step S1 in a beaker, adding 3 mol / L hydrochloric acid solution according to a solid-liquid ratio of 1:6, raising the leaching temperature by 60°C, transferring to a magnetic stirrer and leaching at a speed of 500 rpm for 3 hours, filtering, washing the precipitate, checking with a silver nitrate solution for the absence of chloride ions, collecting the filtrate, and obtaining a barium slag leaching solution;

[0077] S3, adding barium carbonate to the barium slag leachate to neutralize excess hydrochloric acid, adjusting the pH of the leachate to 6.2, then adding 0.5 mol / L barium hydroxide solution dropwise, adjusting the pH to 8.9, precipitating other metal ions in the solution, filtering, performing solid-liquid separation, collecting the filtrate as a high-purity barium solution, collecting the filter residue, adding calcium hydroxide and mixing evenly, adjusting the pH of the filter residue to 8.0, and obtaining a barium sulfate filter residue;

[0078] The preparation method of the reinforced polypropylene fiber specifically comprises the following steps:

[0079] S4. Accurately weigh 1.5 g of acrylic acid and 0.8 g of AMPS in a flask, add 50 mL of anhydrous ethanol and stir until dissolved, adjust the pH to 7, add 10 g of polypropylene to the reaction system, add 20 mg of ammonium persulfate, introduce nitrogen to replace the aerobic environment in the reaction system, raise the temperature of the reaction system to 80° C. in a sealed environment, mix the reaction system thoroughly, react for 15 min, immediately add 3 g of oxidized polyethylene wax and 4 g of vinyl triethoxysilane, mix, and after the reaction system cools to room temperature, dry and remove the solution to obtain a polypropylene fiber precursor;

[0080] S5, placing 10 g of the polypropylene fiber precursor prepared in step S4 in a beaker, heating to 50° C., adding 200 mL of the high-purity barium solution prepared in step S3, placing on a stirrer, stirring at a speed of 450 rpm, raising the reaction temperature to 100° C., continuing to stir the reaction for 100 min, and after the reaction system is cooled to room temperature, freeze-drying to remove excess solvent to obtain a polypropylene blend;

[0081] S6, placing the enhanced polypropylene blend prepared in step S5 in a dynamic vacuum oven for drying, extruding it at a temperature of 220-224° C. using a twin-screw common mixing extruder, spinning it with a pore size of 0.3-0.5 mm, and cutting it into enhanced polypropylene fibers with a length of 80 mm;

[0082] The present invention also provides a preparation method using barium sulfate waste residue and wall filling material, which specifically comprises the following steps:

[0083] S7, mixing the coarse aggregate, barium sulfate waste residue and cement at a speed of 40 rpm for 1 min;

[0084] S8, add water reducing agent and water, stir at 60 rpm, and mix well;

[0085] S9. Add reinforced polypropylene fiber and stir at 80 rpm to obtain a wall filling material.

[0086] Comparative Example 1

[0087] This comparative example provides a wall filling material and a preparation method thereof, which is different from Example 1 only in that the preparation method does not include step S5, and the remaining components, component contents and preparation method are the same as those in Example 1.

[0088] Comparative Example 2

[0089] This comparative example provides a wall filling material and a preparation method thereof, which differs from Example 1 only in that step S4 of the preparation method is to accurately weigh 8g of polypropylene and put it into a beaker, introduce nitrogen into the beaker to replace the aerobic environment in the reaction system, raise the temperature of the reaction system to 80°C in a sealed environment, add 1g of oxidized polyethylene wax and 3g of vinyl triethoxysilane, mix them, and after the reaction system cools to room temperature, dry and remove the solution to obtain a polypropylene fiber precursor, that is, the polypropylene fiber is not modified with AMPS and acrylic acid, and the remaining components, component contents and preparation method are the same as those in Example 1.

[0090] Experimental Example 1

[0091] In this experiment, the microscopic morphology of the enhanced polypropylene fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2 was observed, and the microscopic morphology of the above three polypropylene fibers was analyzed using an S-4800 field scanning electron microscope;

[0092] Figure 1 The SEM images of the reinforced polypropylene fibers prepared in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention are shown in the figure. Image A is Example 1, Image B is Comparative Example 1, and Image C is Comparative Example 2. The polypropylene fibers prepared in Example 1 grow a large number of stationary phases containing barium ions, which can increase the surface area of ​​the fiber surface and improve the interfacial bonding performance of the polypropylene fibers in the wall filling material, thereby improving the mechanical properties of the wall filling material; the surface of the polypropylene fibers prepared in Comparative Example 1 is smooth; the polypropylene fibers prepared in Comparative Example 2 are uneven in thickness and have a low degree of crosslinking. After being subjected to external force, the wall filling material is subjected to uneven force, which easily causes wall cracking.

[0093] Experimental Example 2

[0094] In this experimental example, the mechanical properties of the wall filling materials prepared in Examples 1-3 and Comparative Examples 1 and 2 were measured. The test size was 100mm×100mm×400mm. The test method was based on the "Test Method for Drying Shrinkage Cracking Performance of Cement Sand Wells and Concrete" GB / T 29417-2012, and the shrinkage performance of the wall filling materials prepared in Examples 1-3 and Comparative Examples 1-2 was tested; the splitting tensile strength of the above-mentioned wall filling material specimens was tested with reference to the "Standard Test Method for Fracture Strength of Adhesives in Bonded Joints" ASTM D3433-1999 (2005). The test instrument was an electro-hydraulic servo testing machine, and the test was carried out at an age of 28d. During the test, the loading rate was 1.2MPa / min;

[0095] Figure 2The shrinkage performance result diagram of the wall filling materials prepared by the experimental examples and comparative examples of the present invention is shown in the figure. As shown in the figure, the specimens of the wall filling materials prepared by the embodiments and comparative examples show a trend of first expanding and then shrinking with age. The reason is the hardening of the cement colloid in the concrete and the evaporation of water. The shrinkage amount of the time described in Examples 1-3 is relatively small, and Comparative Example 1 is the largest. Since there are residual stresses inside Comparative Examples 1 and 2 and the distribution is uneven, the shrinkage amount of the specimens is large. In the embodiments, modified polypropylene fibers are used to disperse the internal stress of the concrete to maintain a high stability, thereby reducing the change.

[0096] Figure 3 The splitting tensile performance result diagram of the wall filling material prepared by the experimental examples and comparative examples of the present invention is shown in the figure. During the loading process, the splitting tensile strength of the wall filling material specimens prepared by the embodiments and comparative examples gradually shows a downward trend. Within 60 minutes, the splitting tensile strength of the material does not change significantly. After 90 minutes, the splitting tensile strength of the wall filling material specimens prepared by comparative examples 1 and 2 increases rapidly, with the lowest being 0.6 MPa and 0.9 MPa. After 240 minutes of testing in the embodiment, the splitting tensile strength is maintained above 1.6 MPa.

[0097] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0098] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A wall filling material using barium sulfate waste residue, characterized in that: The wall filling material comprises the following components in parts by weight: 550-650 parts of coarse aggregate, 200-300 parts of barium sulfate waste residue, 250-300 parts of cement, 1.5-2 parts of polycarboxylate water reducer, 1.5-2 parts of reinforced polypropylene fiber, 80-120 parts of water; The barium sulfate waste residue is obtained by harmless treatment of mineral waste residue, and the specific method includes the following steps: S1, crushing the barium slag to obtain pretreated barium slag; S2, placing the pretreated barium slag described in step S1 in a beaker, adding hydrochloric acid, adjusting the temperature to 60-70° C., placing on a magnetic stirrer at 450-500 rpm for leaching for 2-3 hours, filtering, washing, and collecting the filtrate to obtain a barium slag leaching solution; S3, taking the barium slag leaching solution prepared in step S2, adjusting the pH to 5.8-6.2 with barium carbonate, adjusting the pH to 8.9-9.1 with barium hydroxide solution, filtering, collecting the filtrate as a high-purity barium solution after solid-liquid separation, collecting the filter residue, adding calcium hydroxide, adjusting the pH of the filter residue to 7.5-8, and obtaining barium sulfate waste residue; The preparation method of the reinforced polypropylene fiber specifically comprises the following steps: S4, dissolving AMPS and acrylic acid in anhydrous ethanol, adjusting the pH value to 6.5-7.0, adding polypropylene, adding ammonium persulfate, heating to 80-100°C in a sealed nitrogen environment for reaction for 15-20 minutes, then adding oxidized polyethylene wax and vinyl triethoxysilane, mixing evenly, removing the solution, and obtaining a polypropylene fiber precursor; In step S4, the components in the raw material include, by weight: 1.5-2 parts of acrylic acid, 0.5-0.8 parts of AMPS, 8-10 parts of polypropylene, 1-3 parts of oxidized polyethylene wax, and 3-5 parts of vinyl triethoxy silane; S5, mixing the polypropylene fiber precursor prepared in step S4 with the high-purity barium solution prepared in step S3, stirring at a speed of 400-500 rpm, raising the reaction temperature to 60-80° C., reacting for 80-100 min, removing excess solvent, and obtaining a reinforced polypropylene blend; S6. The enhanced polypropylene blend prepared in step S5 is placed in a dynamic vacuum oven for drying, extruded at a temperature of 220-240° C. using a twin-screw common mixing extruder, and spun by spinneret with a hole diameter of 0.3-0.5 mm, and cut to obtain enhanced polypropylene fibers.

2. The wall filling material using barium sulfate waste residue according to claim 1, characterized in that: In step S1, the grinding fineness of the pretreated barium slag is -0.074, accounting for 70%-80%.

3. The wall filling material using barium sulfate waste residue according to claim 2, characterized in that: In step S2, the concentration of the hydrochloric acid is 2-3 mol / L; the solid-liquid ratio between the pretreated barium slag and the hydrochloric acid is 1:5-7.

4. The wall filling material using barium sulfate waste residue according to claim 3, characterized in that: In step S4, the mass concentration of the acrylic acid in anhydrous ethanol is 25-30 g / L; the mass of the added ammonium persulfate is 1.25%-1.5% of the acrylic acid.

5. The wall filling material using barium sulfate waste residue according to claim 4, characterized in that: In step S5, the amount of polypropylene fiber precursor added to the high-purity barium solution is 50-70 g / L.

6. The wall filling material using barium sulfate waste residue according to claim 5, characterized in that: In step S6, the length of the reinforced polypropylene fiber is 50-80 mm.

7. The method for preparing a wall filling material using barium sulfate waste residue according to any one of claims 1 to 6, characterized in that: The specific steps include: S7, mixing the coarse aggregate, barium sulfate waste residue and cement at a speed of 40 rpm for 1-2 minutes; S8, add water reducing agent and water, stir at 60-65rpm, and mix well; S9. Add reinforced polypropylene fiber and stir at 80-85 rpm to obtain a wall filling material.

Citation Information

Patent Citations

  • Barium sulfate waste residue comprehensive utilization method and wall filling material

    CN105236783A

  • Method for recovering barium sulfate from solid waste barium-containing salty mud

    CN115676868A